Nutritional considerations in exercise-based heat acclimation: a narrative review - Rosbrook, P.; Margolis, L. M.; Pryor, J. L. (Sports Medicine, 2024)
In addition to its established thermoregulatory and cardiovascular effects, heat stress provokes alterations in macronutrient metabolism, gastrointestinal integrity, and appetite. Inadequate energy, carbohydrate, and protein intake have been implicated in reduced exercise and heat tolerance. Classic exercise heat acclimation (HA) protocols employ low-to-moderate-intensity exercise for 5-14 days, while recent studies have evolved the practice by implementing high-intensity and task-specific exercise during HA, which potentially results in impaired post-HA physical performance despite adequate heat adaptations. While there is robust literature demonstrating the performance benefit of various nutritional interventions during intensive training and competition, most HA studies implement few nutritional controls. This review summarizes the relationships between heat stress, HA, and intense exercise in connection with substrate metabolism, gastrointestinal function, and the potential consequences of reduced energy availability. We discuss the potential influence of macronutrient manipulations on HA study outcomes and suggest best practices to implement nutritional controls.